2017
DOI: 10.15195/v4.a1
|View full text |Cite
|
Sign up to set email alerts
|

Important Matters in Political Context

Abstract: Abstract:The 2004 General Social Survey (GSS) reported significant increases in social isolation and significant decreases in ego network size relative to previous periods. These results have been repeatedly challenged. Critics have argued that malfeasant interviewers, coding errors, or training effects lie behind these results. While each critique has some merit, none precisely identify the cause of decreased ego network size. In this article, we show that it matters that the 2004 GSS-unlike other GSS surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Additionally, there is evidence that the content of individuals' discussions with others that is identified as "important" is shaped by the survey context (Bailey & Marsden, 1999). 1 Similar contextual effects on the content of discussions individuals report having with others are observed in studies fielded during major elections (Lee & Bearman, 2017). 2 In this study, we use both the important matters and the political matters network name generators to measure how healthy our social networks were during the fall of the 2016 U.S. presidential election.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, there is evidence that the content of individuals' discussions with others that is identified as "important" is shaped by the survey context (Bailey & Marsden, 1999). 1 Similar contextual effects on the content of discussions individuals report having with others are observed in studies fielded during major elections (Lee & Bearman, 2017). 2 In this study, we use both the important matters and the political matters network name generators to measure how healthy our social networks were during the fall of the 2016 U.S. presidential election.…”
Section: Introductionmentioning
confidence: 87%
“…But, we also present the raw proportion without excluding relative ties in parenthesis. interviewer effects, survey mode, the role of election context, survey design, the wording of name generators, and so on (Bailey & Marsden, 1999;Brashears, 2011;Fischer, 2009;Lee & Bearman, 2017;Marsden, 1990;Matzat & Snijders, 2010;McPherson et al, 2006;McPherson et al, 2009;Paik & Sanchagrin, 2013). We consider these challenges seriously and explain how we address each challenge below.…”
Section: Potential Challengesmentioning
confidence: 99%
“…Citizens' scant political interest, knowledge and engagement is often regarded as an obstacle to political deliberation (Converse 1963;Carpini and Keeter 1993;Verba, Schlozman, and Brady 1995). Indeed, Americans prefer to talk of other matters than politics (Bearman and Parigi 2004;Small 2013, Lee andBearman 2017). However, even occasional political conversations can provide information (Katz and Lazarsfeld 1955;Huckfeldt 2001;Parker, Parker, and McCann 2008) and serve as heuristics for political decision-making (Gigerenzer and Gaissmaier!2011;Baldassarri 2012).…”
Section: Political Network and Conversationsmentioning
confidence: 99%
“…Could you tell me whether or not you are a member of each type?" The list includes fraternal groups, service clubs, veterans' groups, political clubs, labor unions, sports groups, youth groups, school service groups, hobby or garden clubs, school fraternities or sororities, nationality groups, farm organizations, literary, art, discussion or study groups, 1 The rise in network isolation observed in the 2004 GSS data has been analyzed in great detail (e.g., Lee and Bearman 2016;Paik and Sanchagrin 2013). The present findings concerning personal networks are substantively unchanged if the 2004 data are omitted from multiyear regressions presented here.…”
Section: Informal Socializing and Community Tiesmentioning
confidence: 99%